1991
DOI: 10.1364/ol.16.001747
|View full text |Cite
|
Sign up to set email alerts
|

Pr^3+-doped fluoride fiber amplifier operating at 131 μm

Abstract: We propose what is to our knowledge the first use of a Pr(3+)-doped fluoride fiber amplifier as a practical amplifier operating at the 1.3-microm band, based on a demonstration of signal amplification and a spectroscopic investigation. The feasibility of the fluoride fiber amplifier is confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(52 citation statements)
references
References 10 publications
1
51
0
Order By: Relevance
“…In Table 3 the (s e 2 s ESA ͒t e product (which determines the pump power efficiency of a fiber amplifier) and other radiative parameters for various sulfide glasses and ZBLAN are listed. 1,2,4,16,17 The (s e 2 s ESA ͒t e product of (GeS 2 ) 80 (Ga 2 S 3 ) 20 chalcogenide glass is 250 3 10 226 cm 2 s, comparable with that of Ga-La sulfide glass 1 and nearly seven times that of ZBLAN. This would provide for high pump power efficiencies of the order of 1 dB͞mW with adequate fiber design parameters.…”
Section: Sulfide Glasses Doped With Prmentioning
confidence: 81%
See 1 more Smart Citation
“…In Table 3 the (s e 2 s ESA ͒t e product (which determines the pump power efficiency of a fiber amplifier) and other radiative parameters for various sulfide glasses and ZBLAN are listed. 1,2,4,16,17 The (s e 2 s ESA ͒t e product of (GeS 2 ) 80 (Ga 2 S 3 ) 20 chalcogenide glass is 250 3 10 226 cm 2 s, comparable with that of Ga-La sulfide glass 1 and nearly seven times that of ZBLAN. This would provide for high pump power efficiencies of the order of 1 dB͞mW with adequate fiber design parameters.…”
Section: Sulfide Glasses Doped With Prmentioning
confidence: 81%
“…The product of s e t e determines, along with fiber design parameters, the small-signal gain coefficient or pump power efficiency of a fiber amplifier. 3 By use of ZBLAN (ZrF 4 -BaF 2 -LaF 3 -AlF 3 -NaF) fluoride glass, fiber amplifiers have already been developed, 4,5 with 0.2 dB͞mW as a typical pump power efficiency. Here we report on the photoluminescence properties of Pr 3+ -doped GeS x -based glasses and assess the attainability of highly efficient fiber amplifiers.…”
Section: Sulfide Glasses Doped With Prmentioning
confidence: 99%
“…26 The internal gain is defined by 10 log͑I / I 0 ͒ where I and I 0 represent the optical signal with and without a pumping source, respectively. 27 In the process of gain measurement, it was observed that the continued laser irradiation may lead to a glass temperature rise. It may an induce measurement error which was estimated to be about 0.2 dB.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Lanthanide-based NIR emitters are also used for optical amplification in lasers [10] and silica-based fiber optic networks, for which the emission wavelengths (1330 nm for Pr III and 1550 nm for Er III ) match the "window of transparency" in silica used for telecommunication. [11] Potential applications are thus obvious, but designing efficient sensitization for lanthanide-based NIR emitters remains a challenge, because the Laporte-forbidden 4f!4f transitions prevent direct excitation of the photoluminescence. [10] For Pr III , Nd III , and Er III , the plethora of accessible excited levels in the 6000-35000 cm À1 range is compatible with indirect sensitization processes, during which a suitable aromatic chromoAbstract: Inert and optically active pseudo-octahedral Cr III N 6 and Ru II 6 (Ln = Nd, Eu, Yb, Lu) and [RuLnL 3 ]-(CF 3 SO 3 ) 5 (Ln = Eu, Lu) demonstrate that the helical structure can accommodate metal ions of different sizes, without sizeable change in the intermetallic M···Ln distances.…”
Section: Introductionmentioning
confidence: 99%